Development Of Resource Sharing E-Magazine At SMKN 3 Payakumbuh Using PHP Programming Language - Wahyudi, Wahyudi; Stephane, Ilfa; Roza, Silvia (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2015)
The school magazine at SMK N 3 Payakumbuh still a print magazine that is affixed to wall and less attractive to students. The existence of online media such as e-Magazine as a resource sharing and substitute for print magazine are expected to disseminate information up to date is also made more attractive and spread information quickly without having to look directly magazine that there was a wall at school. Based on these problems then do a needs assessment to collect data as well as interviews, ADDIE methodology used. It can be concluded that it has succeeded in making e-Magazine on SMK 3 Payakumbuh. The goal is to enhance the readers interest in school magazine and can help provide solutions in development of school magazines. With eMagazine of school easier to disseminate new information about school.